2002
DOI: 10.1002/bem.10053
|View full text |Cite
|
Sign up to set email alerts
|

Calcite microcrystals in the pineal gland of the human brain: First physical and chemical studies

Abstract: A new form of biomineralization has been studied in the pineal gland of the human brain. It consists of small crystals that are less than 20 microm in length and that are completely distinct from the often observed mulberry-type hydroxyapatite concretions. A special procedure was developed for isolation of the crystals from the organic matter in the pineal gland. Cubic, hexagonal, and cylindrical morphologies have been identified using scanning electron microscopy. The crystal edges were sharp whereas their su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
(36 reference statements)
1
27
0
Order By: Relevance
“…The pineal gland contains a number of calcified concretions, called 'brain sand' or 'acervuli' (reviewed by Vigh et al 1998), which consist of calcium carbonate (calcite), in this respect sharing some similarities with otoconia (Baconnier et al 2002). Their numbers increase with age; they may be one outcome of the process of senescence, although they are already found in small numbers in children, and do not seem to be caused by specific pathological processes.…”
Section: Pineal Glandmentioning
confidence: 99%
“…The pineal gland contains a number of calcified concretions, called 'brain sand' or 'acervuli' (reviewed by Vigh et al 1998), which consist of calcium carbonate (calcite), in this respect sharing some similarities with otoconia (Baconnier et al 2002). Their numbers increase with age; they may be one outcome of the process of senescence, although they are already found in small numbers in children, and do not seem to be caused by specific pathological processes.…”
Section: Pineal Glandmentioning
confidence: 99%
“…On the whole, in higher animals, the two mineralization forms are present in the pineal gland: polycrystalline concretions (which are up to several millimeters long, and which drew the attention of anatomists as a proper "brain sand") and microcrystals, the size of which varies from 1 to 20 micrometers. 36,37 Small grains and con-cretions, although probably biologically important, have for a long time slipped from observation. A possibility of reversibility of some concretions is clear from the example of the later disappearance of the "sand" present in the human embryonic anterior pituitary.…”
Section: Pineal Sandmentioning
confidence: 99%
“…Schenka et al (2005) reported some histological gliosarcoma components during the immunophenotypical NG97 characterization, even though immunohistochemical markers in those specimens did not confirm this sarcomatous compound. These electron-dense ellipsoids were similar to the concretion structures presented in pineal gland cells, named as Brain sand and composed of calcium (Baconnier et al, 2002). We believe that just one cell morphotype produces this structure combining intracellular calcium with phosphorus molecules that can be released by cells.…”
Section: Discussionmentioning
confidence: 91%